Seroprevalence of anti-HEV IgG in children: very early exposure in young children in a hyperendemic region - Lisandru Capai; Lisandru Capai; Shirley Masse; Nathanaël Hozé; Dorine Decarreaux; Dorine Decarreaux; Jean Canarelli; Marie-Hélène Simeoni; Xavier de Lamballerie; Alessandra Falchi; Rémi Charrel; Rémi Charrel (Frontiers Media S.A., 2023)
Background and objectivesHepatitis E virus (HEV) can be considered an emerging zoonotic pathogen and is an important cause of acute viral hepatitis in high-income countries. Corsica has been identified as a hyperendemic region for HEV. We aimed to characterize the prevalence of IgG among children and estimate the annual force of infection of HEV.MethodsFrom April 2020 to June 2021, we collected 856 "residual sera" in 13 medical biology laboratories. Sera were tested using the Wantaï HEV IgG assay. Data were weighted according to the distribution by sex and age of the real Corsican population. Serocatalytic models were applied to assess the annual force of infection of HEV.ResultsThe weighted seroprevalence was 30.33% [27.15-34.0]. The seroprevalence was only associated with increasing age (7.25-40.52%; p < 0.001). The annual probability of infection was 5.4% for adults and children above 10-year-old and 2.2% for children under 10 yo.ConclusionOur study demonstrates that in the hyperendemic island of Corsica, (i) exposure of the population to HEV is homogeneous at the spatial level with no difference between genders; (ii) HEV exposure occurs from birth, resulting in 7.4% seropositivity at the age of 4 years; and (iii) super exposure is observed after the age of 9 years. Accordingly, specific studies should be conducted to determine the breadth of the situation identified in our study. The role of the environment and its contamination by domestic or wild swine excreta should be investigated using a One Health approach.